2014
DOI: 10.1371/journal.pone.0084896
|View full text |Cite
|
Sign up to set email alerts
|

Why Publishing Everything Is More Effective than Selective Publishing of Statistically Significant Results

Abstract: BackgroundDe Winter and Happee [1] examined whether science based on selective publishing of significant results may be effective in accurate estimation of population effects, and whether this is even more effective than a science in which all results are published (i.e., a science without publication bias). Based on their simulation study they concluded that “selective publishing yields a more accurate meta-analytic estimation of the true effect than publishing everything, (and that) publishing nonreplicable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 36 publications
0
92
0
1
Order By: Relevance
“…Although the Proteus phenomenon may lead to unbiased effect size estimation, neglecting to publish studies with nonsignificant results is a very inefficient scientific enterprise with problems for statistical modeling of effect sizes (Van Assen, Van Aert, Nuijten, & Wicherts, 2014b, 2014c. Furthermore, even though there are occurrences of the Proteus phenomenon in some fields (Ioannidis, 2011), in psychology the vast majority of studies test if an effect is significantly different from zero, rather than if an effect is significantly different from a previously estimated effect (Fanelli, 2010(Fanelli, , 2012Van Assen, Van Aert, et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Proteus phenomenon may lead to unbiased effect size estimation, neglecting to publish studies with nonsignificant results is a very inefficient scientific enterprise with problems for statistical modeling of effect sizes (Van Assen, Van Aert, Nuijten, & Wicherts, 2014b, 2014c. Furthermore, even though there are occurrences of the Proteus phenomenon in some fields (Ioannidis, 2011), in psychology the vast majority of studies test if an effect is significantly different from zero, rather than if an effect is significantly different from a previously estimated effect (Fanelli, 2010(Fanelli, , 2012Van Assen, Van Aert, et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Eliminating publication bias does not only increase accuracy of effect size estimates, it can also be shown that it is more efficient in terms of the number of studies that have to be conducted to estimate an effect with a certain level of precision (van Assen, van Aert, Nuijten, & Wicherts, 2014a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epistemic goal of the community is to discover that e↵ect. To do so, they perform experimental replications and cumulative meta-analyses (Cumming, 2012;de Winter & Happee, 2013;van Assen et al, 2014). The basic set-up is as follows.…”
Section: Scientific Utopia and Sct* In Silicomentioning
confidence: 99%
“…but "That's funny…" '. Just as negative results in science are a potentially important but underreported resource (Sandercock, 2012;van Assen et al, 2014;Matsuda et al, 2015;Weintraub, 2016), 'engineering failures' in synthetic biology might become a valuable resource if more were published openly rather than being written off as mis-steps.…”
Section: Discussionmentioning
confidence: 99%